Disciplining Ballots? – (Un-intended) Effects of Voter Engagement on the Fiscal Sustainability of Swiss Cantons - Yannick Bury; Lars P. Feld; Ekkehard A. Köhler (Center for Economic Studies and ifo Institute (CESifo), 2023)
We test whether the proactive use of instruments of direct democracy by voters can help to explain fiscal sustainability of 25 Swiss cantons. Using data of all cantonal popular votes since 1977, our results show that the fiscal reaction of cantonal governments to an increase in the debt to GDP ratio of a canton is stronger, the more cantonal voters actively made use of their direct democratic rights in the previous year.
Keywords: H11; H50; D72; 330; direct democracy; political process; fiscal policy